Testing the diagnostic accuracy of a 68Ga-PSMA PET Scan in Early Biochemical Recurrence of Prostate Cancer - Vigna-Taglianti Riccardo; Boriano Alberto; Martini Stefania; Olivero Francesco; Solla Salvatore; Spinelli Lavinia; Gianello Luca; Peano Simona; Merlotti Anna Maria (Forum of Clinical Oncology)
PET-PSMA is currently used for restaging prostate cancer (pCa) after primary surgery or radiotherapy. The PSA levels beyond which it is useful to perform it, in terms of cost-benefit ratio, are not to date clearly defined.